The prevalence of phenylketonuria among children with mental retardation in Kelantan - Omar, Julia (2001)
The prevalence of phenylketonuria (PKU) in Malaysia to date is not known since no study has been conducted to address the subject. The objectives of this study were to determine the prevalence of PKU among the mentally retarded children in Kelantan, to determine the feasibility of carrying out a screening programme for PKU in newborns and to establish a method for PKU screening should the need arise later on. The study was a cross-sectional survey involving all the schools with special programmes for mentally retarded children and community- and clinic-based rehabilitation centers ( CCRC) in Kelantan. All children listed and attended these two institutions were taken as the study samples. A validated questionnaire was used to obtain personal and socioeconomic information of the patients and their families. The questionnaire was collected together with the written consent for the study before the final list of respondents was recorded. Blood spots on filter papers were collected by a finger prick method using automated disposable lancet. Validation of the information in the questionnaire, physical examinations and blood spots collection were done at the respective schools and CCRC. Phenylalanine assays were done using the Bacteria Inhibition Assay (BIA), also known as the Guthrie method. The BIA method was optimized in local laboratory before it is used to test the study samples. A total of 24 schools and 34 CCRC were visited during the study period all over Kelantan. Out of 1715 respondents who returned the questionnaire and consented to take part in the study, only 1568 agreed to have blood spots taken and were present during the blood collections. Other then children with mental retardation, samples were also taken from normal and "lembam and last classes (lembam and LC) children. Out of the 1319 school-based respondents, 239 (18.1%) were mentally retarded and 276 (20.9%) were lembam and LC. All the 396 repondents from CCRC were mentally retarded children. The proportion of boys was significantly higher in school-based mentally retarded, Iembam and LC and CCRC respondents, but lower in the normal group. The majority of the respondents were malays, conforming to the population structure of Kelantan. Household income was significantly lower in the lembam and LC and CCRC respondents compared to the other two groups. Likewise, there was no significant difference in income between the lembam and LC and CCRC respondents, and between the nonnal and school-based mentally retarded respondents. The phenylalanine assays were negative for the 1170 respondents who had their blood spots taken. Although the result was negative, the study respondents constituted of only 5% of the projected population with mental retardation, which were not captured by this study because they did not attend any of the institutions visited. The laboratory technique used was accurate and errors had been systematically addressed and prevented to ensure the results were valid and reliable. Phenylketonuria, given the nature and outcome of the disease, is a considerable problem to both the health and social sectors, and fits the criteria to have a screening programme put in place. However, the negative result of this study requires further investigations to be conducted in the near future to convince the authority as to the need for such an expensive programme. This study should be extended to include patients not covered here and also patients in other states. Perhaps, it will also be beneficial to examine other methods of screening for PKU.